Women rapping revolution : hip hop and community building in Detroit - Farrugia, Rebekah; Hay, Kellie D., 1965- (California series in hip hop studies, 2020)
"Detroit is a city that has long been recognized as a center of musical innovation and social change. Rebekah Farrugia and Kellie D. Hay draw on seven years of fieldwork to illuminate the important role that women in Detroit's hip hop underground have played in mobilizing a grassroots response to political and social pressures at the heart of Detroit's ongoing renewal and development project. Focusing on the women-centered hip hop collective The Foundation, Women Rapping Revolution argues that the hip hop underground is a crucial site where Black women shape subjectivity and claim self-care as a principle of community organizing. Through interviews and sustained critical engagement with artists and activists, this study also articulates the substantial role of cultural production in social, racial, and economic justice efforts"--